Hubungan Tingkat Pendidikan dan Pekerjaan dengan Kejadian Covid-19 di Puskemas Pemurus Dalam Kota Banjarmasin - Fajar Satria Rahman; Farida Heriyani; Ira Nurrasyidah; Meitria Syahdatina Noor; Siti Washilah (Homeostasis, 2022)
Abstract: The incidence of COVID-19 continues to increase, especially in the city of Banjarmasin. The increasing number of cases of COVID-19 is caused by several factors, including sociodemographic risk factors such as level of education and occupation. This study aims to analyze the relationship between education and employment levels with the incidence of COVID-19 at the Pemurus Dalam Health Center in Banjarmasin City. The research method is analytic observational with a case control approach. Sampling using simple random sampling technique with a total sample of 64 patients Pemurus Dalam City Health Center Banjarmasin who have met the inclusion and exclusion criteria, then analyzed using the chi-square test. The results showed that there was a relationship between education level and the incidence of COVID-19 which had a p value of 0.026, and the relationship between work and the incidence of COVID-19 which had a p value of 0.035. The two results show that there is a significant relationship (p value < 0.05) between education and occupation levels with the incidence of COVID-19. Keywords: Incidence, Education, Occupation, COVID-19 Abstrak: Kejadian COVID-19 hingga saat ini terus meningkat terutama di Kota Banjarmasin. Meningkatanya kasus kejadian COVID-19 disebabkan oleh beberapa faktor, antara lain faktor risiko sosiodemografik seperti tingkat pendidikan dan pekerjaan. Penelitian ini bertujuan untuk menganalisis hubungan tingkat pendidikan dan pekerjaan dengan kejadian COVID-19 di Puskesmas Pemurus Dalam Kota Banjarmasin. Metode penelitian adalah observasional analitik dengan pendekatan case control. Pengambilan sampel menggunakan teknik simple random sampling dengan jumlah sampel sebanyak 64 pasien Puskesmas Pemurus Dalam Kota Banjarmasin yang telah memenuhi kriteria inklusi dan eksklusi, selanjutnya dianalisis menggunakan uji chisquare. Hasil penelitian menunjukan terdapat hubungan antara tingkat pendidikan dengan kejadian COVID-19 yang memiliki p value sebesar 0,026, dan hubungan antara pekerjaan dengan kejadian COVID-19 yang memiliki p value sebesar 0,035. Kedua hasil tersebut menunjukkan bahwa terdapat hubungan yang bermakna (p value < 0,05) antara tingkat pendidikan dan pekerjaan dengan kejadian COVID-19. Kata-kata kunci: kejadian, tingkat pendidikan, pekerjaan, COVID-19